Value Chain Development and the Agrarian Question: Actor Perspectives on Native Potato Production in the Highlands of Peru1. (15th October 2018) - Tobin, Daniel; Glenna, Leland
Abstract: Value chain development seeks to integrate smallholder farmers into competitive markets to promote economic and social development. This article, conceptually based on the agrarian question, considers how the perspectives of various value chain actors, with particular focus on smallholders, have important implications for the outcomes of these market‐oriented initiatives. Utilizing Long's concept of social interface, we present a mixed‐methods case study that analyzes how smallholders, an NGO, and agrifood corporations, including PepsiCo, partnered to establish value chains for native potatoes in the Peruvian highlands. We find that a thorough understanding of the various perspectives held by value chain actors provides important insight into why value chain initiatives have divergent trajectories. Based on the findings, we conclude that accounting for how actors are responding to development initiatives and one another helps explain development outcomes and that therefore the agrarian question remains relevant in current agricultural development discourse and practice.